2012
DOI: 10.1097/rti.0b013e31822641c9
|View full text |Cite
|
Sign up to set email alerts
|

3D-CT Lung Volumetry Using Multidetector Row Computed Tomography

Abstract: Pulmonary function results, particularly DLCO, were primarily affected by the NLVs of the lower lobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…7,8 These measures are commonly reported in clinical investigation and have been shown to correlate with spirometric and clinical measures of disease. [9][10][11][12] Little attention has been paid, however, to using chest CT scans to determine the normal range of lobe volumes at full infl ation and relaxed exhalation. Once such models have been developed, investigators could then determine the absolute amount of lobe-specifi c hyperinfl ation present on the inspiratory scan (ie, how much lobe volume exceeds predicted at full infl ation) and the lobe-specifi c volume of gas trapped on an expiratory CT image.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These measures are commonly reported in clinical investigation and have been shown to correlate with spirometric and clinical measures of disease. [9][10][11][12] Little attention has been paid, however, to using chest CT scans to determine the normal range of lobe volumes at full infl ation and relaxed exhalation. Once such models have been developed, investigators could then determine the absolute amount of lobe-specifi c hyperinfl ation present on the inspiratory scan (ie, how much lobe volume exceeds predicted at full infl ation) and the lobe-specifi c volume of gas trapped on an expiratory CT image.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a threshold of −950 HU as proposed in previous studies 2022. Furthermore, we used the software for semiautomatic segmentation of the lung into the lung lobes (left upper lobe, left lower lobe, right upper lobe, right middle lobe, and right lower lobe) as described in the literature 19,23. See also example in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective studies of the VENT results indicated that post-procedure lung function improvement did not differ significantly when an upper or lower lobe was treated (42,43). However, recent studies have found that each lobe plays a different role in lung functioning, with the lower lobe of the lung having more of an impact on FEV 1 than the upper lobe (44,45). Therefore, EBV implantation in the lower lobe may have more of a benefit, but this contention needs to be verified.…”
Section: Other Predictorsmentioning
confidence: 99%